Association between protein-to-energy ratio and overweight/obesity in children and adolescents in the United States: a cross-sectional study based on NHANES - Zhao, Feng; Wang, Yudan; Liu, Zhaoyi; Wang, Jiao; Xia, Yinyin; Jiang, Xuejun; Zhou, Lixiao; Khan, Ahmad; Cheng, Shuqun; Zou, Zhen; Chen, Chengzhi; Qiu, Jingfu (Frontiers in Pediatrics, 2024)
The dietary protein proportion may be crucial in triggering overweight and obesity among children and adolescents.: Cross-sectional data from 4,336 children and adolescents who participated in the National Health and Nutrition Survey (NHANES) between 2011 and March 2020 were analyzed. Multivariate logistic regression was used to calculate odds ratio (OR) and 95% confidence interval (CI). Restricted cubic splines assessed the nonlinear relationships between dietary protein intake and the prevalence of overweight and obesity.Results: Adjusted logistic regression models showed that each 1% increase in dietary protein proportion was associated with a 4% higher risk of overweight and obesity (OR=1.04, 95%CI: 1.01-1.07). A nonlinear relationship was noted in children aged 6-11 years (P <0.05), as demonstrated by restricted cubic spline analysis. After dividing dietary protein intake into quartiles, the highest quartile had an adjusted OR of 2.07 (95%CI:1.35, 3.16, P =0.001) compared to the lowest, among children aged 6-11 years.Dietary protein intake is positively linked to overweight and obesity in American children, irrespective of individual characteristics and total energy consumption.